Attention Modulates Neural Responses to Unpredictable Emotional Faces in Dorsolateral Prefrontal Cortex - Ran, Guangming; Chen, Xu; Zhang, Qi; Ma, Yuanxiao; Zhang, Xing (Frontiers in Human Neuroscience, 2016)
Unpredictability about upcoming emotional events disrupts our ability to prepare for them and ultimately results in anxiety. Here, we investigated how attention modulates the neural responses to unpredictable emotional events. Brain activity was recorded using functional magnetic resonance imaging (fMRI) while participants performed a variation of the emotional task. Behaviorally, we reported a fear-unpredictable effect and a happy-unpredictable effect. The fMRI results showed increased activity in the right dorsolateral prefrontal cortex (dlPFC) for unpredictable fear faces (Experiment 1) and decreased activity in the left dlPFC for unpredictable happy faces (Experiment 2) when these faces were unattended, probably reflecting that unpredictability amplifies the negative impact of fear faces and reduces the positive impact of happy faces. More importantly, it was found that the right dlPFC activity to unpredictable fear faces was diminished (Experiment 1) and the left dlPFC activity to unpredictable happy faces was enhanced (Experiment 2) when these faces were attended. These results suggest that attention may contribute to reducing the unpredictability about future emotional events.